2020
DOI: 10.1109/access.2020.3024676
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study and Comparative Analysis of Hybrid Renewable Power System for off-Grid Rural Electrification in a Typical Remote Village Located in Nigeria

Abstract: The introduction of a decentralized energy system in remote rural areas with limited or no access to power supply can improve the quality of life of people living in these areas. Renewable energy technology can play a key role in electricity generation, as grid expansion is not a cost-effective option. In this study, we focused on the techno-economic feasibility and optimal design of a hybrid micro-hydro-photovoltaic-diesel-battery-wind power system designed to electrify a typical remote village located in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…The study did not mention the potential for power availability from renewable resources. Depending on renewable energy technology can not only solve the reliability and economic feasibility of electricity generation, but it can also improve the quality of life of people considering the availability of the resource [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study did not mention the potential for power availability from renewable resources. Depending on renewable energy technology can not only solve the reliability and economic feasibility of electricity generation, but it can also improve the quality of life of people considering the availability of the resource [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For an optimal mixture of different renewable energy sources, researchers use various hybrid system optimization methods and some types of software, including linear programming, artificial intelligence, MATLAB/Simulink, and HOMER [7]. e authors in [8] discussed the feasibility of the hydro/PV/wind/diesel system using HOMER simulation software, and others in [8,9] discussed the feasibility study and comparative analysis of hybrid renewable power system for off-grid. In [10], Yibo et al designed a hydro/PV hybrid power system in an isolated microgrid.…”
Section: Research Backgroundmentioning
confidence: 99%
“…The multiyear analysis revealed that the system consisting of a PV, diesel generator, and battery HES under the LF strategy is the most preferred combination. In [29], the system including a PV, wind turbine, hydropower, diesel generator, and battery was examined from the technical and economic perspectives for The selection of the optimal system component sizes requires a detailed analysis of the availability of RESs, suitable control methods, and a system's hardware components [20]. Energy management control systems are required for the purpose of operation, integration, and interconnection of different components in a single generation system and for ensuring safe operations and achieving the set goals.…”
Section: Introductionmentioning
confidence: 99%
“…The multiyear analysis revealed that the system consisting of a PV, diesel generator, and battery HES under the LF strategy is the most preferred combination. In [29], the system including a PV, wind turbine, hydropower, diesel generator, and battery was examined from the technical and economic perspectives for the electrification of a remote village in Nigeria. The energy flow control among the components was achieved using the LF strategy.…”
Section: Introductionmentioning
confidence: 99%